1997
DOI: 10.1021/ic961289h
|View full text |Cite
|
Sign up to set email alerts
|

Solvothermal Synthesis of a New Mixed-Metal Polysulfide Cluster, [Me4N]3[MoS4Cu3(S5)2]

Abstract: A new mixed-metal polysulfide complex, [Me4N]3[MoS4Cu3(S5)2], has been synthesized and structurally characterized. The tetranuclear trianion has C 2 symmetry, and the boat−chair eight-membered metallacyclic S5Cu2S rings interact through S···S weak interaction to form infinite chains along the [201] direction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

1997
1997
2010
2010

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(5 citation statements)
references
References 31 publications
0
5
0
Order By: Relevance
“…Müller et al. have demonstrated that the terminal sulfide ligands in MoS 4 2- readily bind to CuCN to afford both dinuclear [MoS 4 (CuCN)] 2- and trinuclear [MoS 4 (CuCN) 2 ] 2- complexes 6a. However, the reaction of [MoO 2 S 2 ] 2- with CuCN afforded exclusively the dinuclear complex 1 , since the terminal oxo ligands have lower affinity toward late transition metals because of their hard character.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Müller et al. have demonstrated that the terminal sulfide ligands in MoS 4 2- readily bind to CuCN to afford both dinuclear [MoS 4 (CuCN)] 2- and trinuclear [MoS 4 (CuCN) 2 ] 2- complexes 6a. However, the reaction of [MoO 2 S 2 ] 2- with CuCN afforded exclusively the dinuclear complex 1 , since the terminal oxo ligands have lower affinity toward late transition metals because of their hard character.…”
Section: Resultsmentioning
confidence: 99%
“…We have chosen the latter strategy since molybdenum sulfide complexes with one dithiolene ligand are unknown. 4a-c A logical starting point for the construction of the dinuclear Mo−Cu unit is to use simple thiomolybdates, [MoO 4 - n S n ] 2- ( n = 1−4), since they have remarkable affinity toward transition metals. Thus, the reaction with copper complexes readily takes place to form various types of multinuclear Mo−Cu complexes, , including dinuclear [S 2 MoS 2 Cu(CN)] 2- , 6a, [S 2 MoS 2 Cu(SAr)] 2- , and [OSMoS 2 Cu(CN)] 2- …”
Section: Introductionmentioning
confidence: 99%
“…The average S−S distance within the S 5 2- polyanion is 2.071 Å with a bonding pattern “long−short−medium−medium” (see Table ). Depending on the actual bonding mode, other sequences were reported. …”
Section: Resultsmentioning
confidence: 99%
“…In KAuS 5 the two terminal S atoms connect two Au centers leading to the formation of 1D chains . In [Me 4 N] 3 [MoS 4 Cu 3 (S 5 ) 2 ] the two S 5 2- anions bridge across a pair of Cu atoms to form a S 5 Cu 2 S metallacycle . A bidentate behavior was reported for (PPh 4 ) 2 [Te(S 5 ) 2 ] .…”
Section: Resultsmentioning
confidence: 99%
“…Development in the chemistry of molybdenum sulfides started with the initial reports on the synthesis and structure of [(S 2 ) 2 Mo(μ-S 2 )] 2 2- 21a and [Mo 3 S 13 ] 2- 21b by Müller et al Numerous complexes containing the dimeric [M 2 X 2 (μ-E) 2 ] core are now generally prepared by the following synthetic methods: (1) reaction of [MS 4 ] 2- (M = Mo, W) with sulfur or organic polysulfides, ,9b,,17a in which an externally induced internal redox pathway has been proposed as the mechanism for the formation of dimeric complexes; (2) an intramolecular redox process based on the acidification or heating of the tetrathiomolybdates/tetrathiotungstates/tetraselenidotungstates; 11a,12e,h,19b and (3) interconversion of various isomers of [M 2 E n ] 2- (M = Mo, W; E = S, Se; n = 6−12) by addition or removal of sulfur or selenium. 2b,8a,9a,,,17a,19c Recently we became interested in the use of the hydro(solvo)thermal technique for the preparation of transition metal polychalcogenides . In this paper we report the solvothermal synthesis and structure of the new compound (Et 4 N) 2 [(Mo 2 O 2 Se 6 ) 0.20 (Mo 2 O 2 Se 7 ) 0.18 (Mo 2 O 2 Se 8 ) 0.62 ], in which the major component ion [Mo 2 O 2 (μ-Se) 2 (Se 2 )(Se 4 )] 2- is found for the first time.…”
Section: Introductionmentioning
confidence: 99%